1998
DOI: 10.1074/jbc.273.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrin-activated Pathway Forms PKB/Akt- stimulatory Phosphatidylinositol 3,4-Bisphosphate via Phosphatidylinositol 3-Phosphate in Platelets

Abstract: The aggregation of human platelets is an important physiological hemostatic event contingent upon receptordependent activation of the surface integrin ␣ IIb ␤ 3 and subsequent binding of fibrinogen. Aggregating platelets form phosphatidylinositol 3,4-bisphosphate (PtdIns(3,4)P 2 ), which has been reported to stimulate in vitro the activity of the proto-oncogenic protein kinase PKB/Akt, as has phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ). It has been assumed that PtdIns(3,4)P 2 is synthesized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
3
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 28 publications
(38 reference statements)
4
142
3
1
Order By: Relevance
“…However, the finding that agonists, such as hydrogen peroxide [30], and crosslinking of platelet-integrin receptors [31] elevate PtdIns(3,4)P # , without increasing PtdIns(3,4,5)P $ , suggest that PtdIns(3,4)P # may be able to regulate physiological processes distinct from those controlled by PtdIns(3,4,5)P $ . TAPP1 and TAPP2 ( Figure 3) are the first proteins to be identified that interact with PtdIns(3,4)P # specifically, and may therefore be key mediators of cellular responses that are regulated specifically by this second messenger.…”
Section: Discussionmentioning
confidence: 95%
“…However, the finding that agonists, such as hydrogen peroxide [30], and crosslinking of platelet-integrin receptors [31] elevate PtdIns(3,4)P # , without increasing PtdIns(3,4,5)P $ , suggest that PtdIns(3,4)P # may be able to regulate physiological processes distinct from those controlled by PtdIns(3,4,5)P $ . TAPP1 and TAPP2 ( Figure 3) are the first proteins to be identified that interact with PtdIns(3,4)P # specifically, and may therefore be key mediators of cellular responses that are regulated specifically by this second messenger.…”
Section: Discussionmentioning
confidence: 95%
“…Major signaling molecules lying downstream of G protein activation include PKC (4), MEKK1 (41), PI 3-kinase (25,26), and p160 ROCK (23,24), among many others (3). We measured the effects of selective inhibitors for these molecules on platelet aggregation stimulated by combined G 12/13 and G i signaling.…”
Section: Signaling Events Downstream Of Concomitant Activation Of G Pmentioning
confidence: 99%
“…The ␣-subunit of the heterotrimeric G protein G i pathway inhibits the activity of adenylyl cyclase while the ␤␥-subunit activates PI 3-kinase (25). Together, these pathways lead to the activation of numerous kinases including protein kinase B (PKB/Akt) (26), PKC (4), Map kinase kinase (MEKK1) (27), Src family tyrosine kinases (28), among many others.…”
mentioning
confidence: 99%
“…4,4,5)P 3 ] is a transient plasma membrane (PM) signal, rapidly hydrolyzed to phosphatidylinositol-(3,4)-bisphosphate [PtdIns(3,4)P 2 ] by the inositol polyphosphate 5-phosphatases (5-phosphatases) (Stephens et al, 1993;Mitchell et al, 2002). PtdIns(3,4)P 2 is a more sustained signal lasting for up to 60 min, stimulated by B-cell activation, oxidative stress, or irreversible platelet aggregation (Banfic et al, 1998;Van der Kaay et al, 1999;Marshall et al, 2002).…”
Section: Introductionmentioning
confidence: 99%